A Postmortem Study of the Pyramidal lobe of the Thyroid Gland in Bangladeshi People (Journal of Dhaka Medical College, 2010)
Background: The pyramidal lobe is also called the 3rd lobe of the thyroid gland which ascends toward the hyroid bone from the isthmus or the adjacent part of either lobe. A fibrous or fibromascular band the levetor glandulae thyroideae occasionally extends upwards from the apex of the pyramidal lobe to the body of the hyoid bone. Any pathology of thyroid gland involves this lobe, some pathology started from here or recurrence may occur from this lobe. Anatomical knowledge about pyramidal lobe is essential for surgeons, endocrinologists, pathologists and sonologists for proper diagnosis and management of thyroid diseases. Study design: Cross sectional descriptive type of study. Place and period of study: Department of Anatomy, Sir Salimullah Medical College, Dhaka. Study period was from July 2003 to June 2004. Materials: The study was done by examining 60 post mortem human thyroid glands, age ranging from 7 to 67 years. The glands were collected from unclaimed dead bodies autopsied in the morgue of Dhaka Medical College and Sir Salimullah Medical College under the department of Forensic Medicine. Methods: The collected sample were grouped in to three age groups including group A(0-20 years), group B (21-50 years) and group C (>50 years). The presence, variation of position of the pyramidal lobe and its relation with levator glandulae thyroideae were studied. Result: The pyramidal lobe was found in 16 of 60 thyroid glands in different age groups and situated more on the left side than the right. In 9 cases, levator glandulae thyroideae were found. All extended from the apex of the pyramidal lobe to the body of the hyoid bone. Key words: Pyramidal lobe; levator glandulae thyroideae; thyroid gland. DOI: 10.3329/jdmc.v18i2.6270 J Dhaka Med Coll. 2009; 18(2) : 120-123